ANALYSIS OF FIGURATIVE LANGUAGE IN SONG’S LYRIC OF JUICE WORLD - Rohana, Nur Ali (Fakultas Ilmu Budaya and LPPM Universitas Sebelas April, 2024)
This study aimed to identify and analyze the figurative language in Juice Wrld's Wishing Well and Righteous song lyrics. This research also aimed to explain the meaning of the figurative language found in the song lyrics. The method of this research employed the descriptive qualitative method by Cresswell and data collection method by Moleong (2012) and the theory for examining data used by Kennedy (1979). The data analysis procedures included reading the lyrics, identifying, classifying, and explaining the meaning of each figurative language found in the song lyrics. The result of this research showed five types of figurative language were found in song lyrics, such as metaphor, simile, hyperbole, metonymy, and paradox. Nevertheless, metaphor is the most figurative language used appearing a countable total of 34 times, and the least figurative language used is hyperbole with a total of 1 time. Furthermore, four types do not appear in this research, there are metonymy, symbol, irony, and synecdoche.